2016
DOI: 10.1002/jrs.4904
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering characteristics of CuO : Mn/Ag heterojunction probed by methyl orange: effect of Mn2+ doping

Abstract: Interest in the synthesis of hybrid substrates for surface-enhanced Raman scattering (SERS) has surged recently. Hereof, in the present work, a hybrid SERS substrate CuO : Mn/Ag heterojunction has been synthesised. To accomplish this, the nanostructred Ag island film and CuO : Mn nanoparticles are synthesised by vacuum thermal evaporation method and sol-gel method respectively, and thereafter, a heterojunction between the CuO : Mn and Ag is fabricated by adsorption of CuO : Mn (10 -3 M in ethanol) on Ag island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…B. The sample CuO/γ‐Al 2 O 3 prepared by impregnation exhibits Raman bands at 280, 330, 612, and 1100 cm −1 , which agrees well with the monoclinic CuO nanoparticles . It is interesting to note that the cubic CuO nanoparticles prepared by CVD gives a group of completely different Raman peaks at 98, 148, 220, and 635 cm −1 compared with the monoclinic CuO prepared by impregnation.…”
Section: Resultssupporting
confidence: 62%
“…B. The sample CuO/γ‐Al 2 O 3 prepared by impregnation exhibits Raman bands at 280, 330, 612, and 1100 cm −1 , which agrees well with the monoclinic CuO nanoparticles . It is interesting to note that the cubic CuO nanoparticles prepared by CVD gives a group of completely different Raman peaks at 98, 148, 220, and 635 cm −1 compared with the monoclinic CuO prepared by impregnation.…”
Section: Resultssupporting
confidence: 62%
“…This blue shifting of the major Raman bands of MO and CO in CMO@MCO can be ascribed to the local structure distortion of MO and CO induced by doping. 45 , 47 Besides, the intensity reduction with the broadening of the major peaks demonstrates the occurrence of lattice defects by the creation of oxygen vacancies. 45 These results further specify the formation of MO, CO, and CMO@MCO with good crystallinity, which is consistent with the XRD results.…”
Section: Resultsmentioning
confidence: 99%
“…The strongly localized character of the surface plasmon, i.e., its electric field E (r) SP scales with 1/r 3 , limits the probing area down to a few nanometers (d SP ≈ 4-5 nm) [38,39], making the study of the manganite surface by means of Raman spectroscopy in principle possible. However, up to now only a few studies were performed on oxides, mostly focused on nanoparticles rather than thin films [40][41][42]. Moreover, to the best of our knowledge, only one TERS study on a strongly correlated material, the double perovskite La 2 CoMnO 6 [43], was published, but no surface-oriented studies of the mixed-valence manganites, La 1−x A x MnO 3 , were reported up to now.…”
Section: Introductionmentioning
confidence: 99%